Efeitos do programa Promove-Pais, uma terapia comportamental aplicada a cuidadoras de adolescentes com problemas de comportamento - De Carvalho Kanamota, Priscila Ferreira [UNESP]; Bolsoni-Silva, Alessandra Turini [UNESP]; Kanamota, Juliano SetsuoViolin (My University, 2017)
Parental educational practice literature argues that how parents interact with their children can be both a risk factor or a protective factor in child behavioral problems. Parent/caregivers programs are usually carried out in groups including the children's parents. The objective of this study is to describe the effects of the PROMOVE-PAIS program, applied in individual psychotherapy of parents/caregiver of adolescents. The program aims to both promote the extension of positive parental and child social skills as well as the reduction of negative parental practices and adolescent behavioral problems. Two mothers (P1 and P2) and one caregiver (P3) of adolescents with externalizing and/or internalizing behavioral problems, participated in individual psychotherapy, along with a psychologist. The therapy process was comprised of fourteen sessions featuring discussions pertaining to communication, expression of feelings and the establishment of limits. For data collection a quasi-single case-experimental (Pre-test, Post-test and Follow-up) design was applied. The instruments used were the Child Behavior Checklist (CBCL), 6 to 18 years old and the Parental Social Educative Skills Interview Script (RE-HSE-P) at all stages. Gains were observed from the psychotherapeutic intervention in all the parents/caregiver both at the end of the psychotherapeutic process as well as during follow-up evaluations. It was observed that both P1 and P3 experienced an increase in positive educational practices and a reduction of negative educational practices, together with an increase in social skills and a reduction of adolescent behavioral problems. For P2, an expansion of the contexts and subjects of interaction were observed, with an increase in social skills and a reduction of behavioral problems for the adolescent as a result. It was observed that results found in parental group interventions were also found in individual psychotherapy with mothers/caregiver of adolescents. This study collaborates with the area of Evidence-Based Psychotherapy and expands the technology for intervention in the area of parental social educative skills and behavioral problems.
Effects of the Promove-Pais program, a behavioral psychotherapy applied to caregivers of adolescents with behavioral problems
Keywords: Adolescent; Behavioral problems; Parent training; Parental educative social skills; Psychotherapy